Tipificación de las lesiones de tránsito que no superen los tres días de incapacidad, como garantía de los derechos de las víctimas - Morante Jiménez, José Augusto (2020)
Research has led to the determination that there is a large-scale increase in recent years in the incidence of traffic accidents, from which harmful consequences always arise. This is the case of the absence of the legal configuration as a criminal type of the crime of injuries in transit that do not exceed three days of disability, which causes criminal impunity in this case and worse, leaves the victim defenseless, the one that will have to bear the consequences without being able to initiate any criminal proceeding against the person responsible for their injuries, and arises as a result of the formulation of the following investigation problem: The lack of classification as a criminal offense in the Comprehensive Organic Penal Code, of the traffic accident cases that produce injuries, whose incapacity does not exceed three days, will be causing impunity and affecting the rights of the victims?, which evidences the lack of constitutional guarantees, violating the Principle of Legality this is principle fundamental because the laws must be typified because without law there is no crime or penalty and since it is neither criminalized nor as a violation, it is it would take impunity for these infractions; mainly the right of the victim to claim from the state body when they have suffered some type of these minimally disabled injuries, which according to article 82 of the Constitution of the Republic of Ecuador refers to Legal Security and states the following: “The right legal security is based on respect for the Constitution and on the existence of previous, clear, public legal norms applied by the competent authorities. ” Currently, this criminal type does not work in the COIP, and, therefore, any conduct that could configure this contravention would go unpunished because, due to the principle of legality, it could not be judged or sanctioned unless it is previously established in the current criminal law, in this case, in the COIP………………